Southern African Liberation Movements and the Global Cold War 'East'. Transnational Activism 1960-1990 - Dallywater, Lena (Dialectics of the Global, 2019)
This volume explores connections between liberation movements in Southern Africa and between those movements and countries in the Eastern Bloc in the Cold War decades of the 1960s, 1970s, and 1980s. The many different forms such connections took have been little investigated. Articles in this edition enter that research gap and showcase studies of such interactions, seeking to explain why they took the form they did